Reading philosophy, writing poetry intertextual modes of making meaning in early medieval China - Swartz, Wendy 1972- (Harvard-Yenching Institute monograph series, 2018)
In a formative period of Chinese culture, early medieval writers made extensive use of a diverse set of resources, in which such major philosophical classics as Laozi, Zhuangzi, and Classic of Changes featured prominently. Reading Philosophy, Writing Poetry examines how these writers understood and manipulated a shared intellectual lexicon to produce meaning. Focusing on works by some of the most important and innovative poets of the period, this book explores intertextuality―the transference, adaptation, or rewriting of signs―as a mode of reading and a condition of writing. It illuminates how a text can be seen in its full range of signifying potential within the early medieval constellation of textual connections and cultural signs.